2022
DOI: 10.3390/nanomanufacturing2030006
|View full text |Cite
|
Sign up to set email alerts
|

Nano-Titanium Oxide in Polymeric Contact Lenses: Short Communication

Abstract: Many individuals suffer from myopia or hyperopia and astigmatism owing to the refractive defects of the eye optics or because of the use of inappropriate contact lenses. This study dealt with three polymers Poly(methyl methacrylate) (PMMA), Poly(Hydroxyl methacrylate) (PHEMA), and Poly(glycidyl methacrylate) (PGMA) and doping them with TiO2 nanoparticles to evaluate the difference between the effect of each lens on the human eye. The TiO2 NPs were prepared in this work by the sol–gel method to obtain 70–90 nm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 32 publications
0
1
0
Order By: Relevance
“…Shaker et al reported the fabrication of THPN ophthalmic lenses that incorporated commercial TiO 2 NPs into each matrix including poly(methyl methacrylate) (PMMA), poly(hydroxyethyl methacrylate) (PHEMA), and poly(glycidyl methacrylate) (PGMA). 55 The THPN lenses showed improved image clarity and small chromatic aberration. Messaddeq et al proposed a gradient-refractive-index lens with UV polymerization kinetics of the prepolymer.…”
Section: Applications Of Zro 2 Thpn As Transparent Advanced Optical M...mentioning
confidence: 98%
“…Shaker et al reported the fabrication of THPN ophthalmic lenses that incorporated commercial TiO 2 NPs into each matrix including poly(methyl methacrylate) (PMMA), poly(hydroxyethyl methacrylate) (PHEMA), and poly(glycidyl methacrylate) (PGMA). 55 The THPN lenses showed improved image clarity and small chromatic aberration. Messaddeq et al proposed a gradient-refractive-index lens with UV polymerization kinetics of the prepolymer.…”
Section: Applications Of Zro 2 Thpn As Transparent Advanced Optical M...mentioning
confidence: 98%
“…This stability is imperative in averting lens deformation, tearing, or unintended dislodgement, thereby fortifying reliable vision correction. [11,12] Synthesized through diverse manufacturing techniques, including spin casting and molding processes, vinyl polymers enable the production of lenses with precise dimensions, cus-tomized parameters, and unwavering quality. [13] Tailored polymerization techniques further endow these lenses with specific material properties, while surface modification and functionalization methods augment their performance.…”
Section: Brief Introduction To Vinyl Polymers and Their Suitability F...mentioning
confidence: 99%
“…This stability is imperative in averting lens deformation, tearing, or unintended dislodgement, thereby fortifying reliable vision correction. [ 11,12 ]…”
Section: Introductionmentioning
confidence: 99%